A critical reading of the selected poems of T.S. Eliot - Jain, Manju (New Delhi : New York : Oxford University Press, 2003)
T.S. Eliot's poetry is well known for its allusiveness and reference to a wide range of historical and literary subjects. At the same time, the roots of explanations and critical readings necessary to elucidate and contextualize Eliot's poetry have seldom been available. This book offers a carefully explanatory as well as critical reading of Eliot's Selected Poems. It tackles each poem individually, offering comments and explanations that draw from secondary as well as archival and unpublished sources. In particular, there is an exhaustive section explaining and contextualizing the manifold difficulties encountered in The Waste Land. A long Introduction outlines Eliot's life, career and thought, and a Select Bibliography provides up-to-date information on useful secondary literature." "Dr. Jain's use of various new critical approaches, alongside her use of primary data from Eliot holdings in the UK and the USA, makes this an important source for comprehending Eliot's difficult poetry. It will be of great use to students, as well as to people who teach the poetry of T.S. Eliot."--Jacket
Includes bibliographical references.